A Tapped Density Taguchi Optimization for Orange Peel Particulate Green Fillers - Ajibade, Oluwaseyi Ayodele; Agunsoye, Johnson Olumuyiwa; Oke, Sunday Ayoola (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
Transportation of green fillers for composites has serious densification implications due to particulate shape irregularities and size distributions. To date, few scientific studies are available on the tapped density measurements of orange peel particulate fillers. In this work, experiments were conducted on the tapped density of orange peel particulates in gentle and successive taps to the measuring cylinder containing the particulate matter. Taguchi's technique of